THE RELATIONSHIP OF BREASTFEEDING MOTHERS‘ HYGIENE BEHAVIOR WITH THE INCIDENCE OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) - Aning Subiyatin; Rike Syahniar; Adinta Anandani (Poltekkes Kemenkes Semarang, 2022)
Staphylococcus aureus (S.aureus ) is a pathogenic bacterium that can be isolated from breast milk and can cause various infections including pneumonia, sepsis, skin lesions, and food poisoning in infants. This bacterium is present in humans and does not cause any symptoms, but it can serious infections such as sepsis and even death. In nursing mothers, This bacterium is associated with mastitis (breast infection) and abscesses of breasts that require medical attention. The purpose of this study was to determine the factors of breastfeeding behavior with the incidence of MRSA. This research was an analytical observational with a cross-sectional approach to breastfeeding mothers in the South Tangerang area. The sampling technique used purposive sampling on 47 people—data collection using questionnaires and Vitek-2 examination for MRSA. Hygiene behavior in breastfeeding mothers in the good category 27 (57.4%). Four (8.5%) breastfeeding mothers were positive for MRSA. There was no relationship between hygiene behavior in breastfeeding mothers and MRSA (p=1,000). Hygiene behavior in breastfeeding mothers in South Tangerang was in a good category. There were 8.5% of breastfeeding mothers are MRSA-positive. Hygiene behavior in breastfeeding mothers can prevent the transmission of MRSA to infants.